2022
DOI: 10.1155/2022/8522937
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial and Healing Effect of Scrophularia striata Boiss Hydroalcoholic Extract on First- and Second-Grade Pressure Wounds in Patients with Brain and Spinal Cord Injury: A Randomized Clinical Trial

Abstract: Introduction and Objectives. Pressure wound is one of the most common problems in patients with brain and spinal cord lesions leading to complications such as severe pain, infection, and frequent hospitalisation. The present study aimed to determine the restorative and antimicrobial effects of Scrophularia striata hydroalcoholic extract (SHE) on first- and second-grade pressure ulcers in patients with brain and spinal cord lesions. Materials and Methods. This double-blind clinical trial study was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The National Pressure Ulcer Advisory Panel (NPUAP), at its academic meeting on 8 April 2016, defined a PU as a localised injury to the skin and deep soft tissues located at the site of a bony prominence or associated with a medical device, which can present as an intact skin or open breakout accompanied by pain 2 . PUs have a high prevalence in countries all over the world, with approximately 2.5 million occurring annually in the United States; they affect 23.1% of hospitalised patients in the Netherlands, 21.8% in the United Kingdom and 44% in Iran 3–6 . Traumatic brain injury (TBI) is often caused by traffic accidents or accidental violence, and it often requires surgical treatment to ensure the patient's physical stability 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Pressure Ulcer Advisory Panel (NPUAP), at its academic meeting on 8 April 2016, defined a PU as a localised injury to the skin and deep soft tissues located at the site of a bony prominence or associated with a medical device, which can present as an intact skin or open breakout accompanied by pain 2 . PUs have a high prevalence in countries all over the world, with approximately 2.5 million occurring annually in the United States; they affect 23.1% of hospitalised patients in the Netherlands, 21.8% in the United Kingdom and 44% in Iran 3–6 . Traumatic brain injury (TBI) is often caused by traffic accidents or accidental violence, and it often requires surgical treatment to ensure the patient's physical stability 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 PUs have a high prevalence in countries all over the world, with approximately 2.5 million occurring annually in the United States; they affect 23.1% of hospitalised patients in the Netherlands, 21.8% in the United Kingdom and 44% in Iran. 3 , 4 , 5 , 6 Traumatic brain injury (TBI) is often caused by traffic accidents or accidental violence, and it often requires surgical treatment to ensure the patient's physical stability. 7 Among the TBI, severe TBI is the most critical craniocerebral injury, which is characterised by rapid progression, lack of significant therapeutic effect and high rates of disability and death.…”
Section: Introductionmentioning
confidence: 99%
“…S. striata has been traditionally used for its potent anti-inflammatory and healing effects. Previous studies showed that the extract obtained from this plant can increase fibroblast proliferation and promote tissue re-epithelialization [18]. Q. infectoria galls extract is also a potent astringent and anti-inflammatory agent, and both of these properties are considered useful in periodontal diseases.…”
Section: Anticariogenicity Of the Herbal Mouthwashmentioning
confidence: 99%
“…Scrophularia striata is a small flowering plant that is native to Iran and some parts of Turkey and Azerbaijan [16][17][18]. This plant exhibits several pharmacological activities, including antiproliferative, wound healing, anti-inflammatory, antioxidant, neuroprotective, analgesic, and preservative activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation